2018
DOI: 10.5897/ajmr2018.8988
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of bloodstream infection in Saudi Arabia

Abstract: Bloodstream infections are a challenge to clinicians due to high rates of morbidity and mortality. Moreover, rational antimicrobial therapy, if promptly started, can improve the prognosis of sepsis. The gold-standard blood culture has some limitations and it takes time to complete (about 2-5 days). This leaves the clinicians to start immediately broad-range antimicrobial therapy until microbiology culture's results available that may lead to complicate situation of patient further. Therefore, there is an urgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…These findings are in agreement with those of Tian et al [ 27 ], who isolated several clinical bacterial strains from Chinese patient blood samples, including S. aureus , E. coli , K. pneumoniae , and S. typhi . In addition, Ozbak [ 8 ] showed that the most commonly isolated bacteria in Saudi Arabia were S. aureus and CoNS, among the gram-positive, and E. coli , K. pneumoniae , and P. aeruginosa , among the gram-negative. Moreover, Akova [ 16 ] reported that E. faecium , S. aureus , K. pneumoniae , A. baumannii , P. aeruginosa , E. coli , and Enterobacter spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are in agreement with those of Tian et al [ 27 ], who isolated several clinical bacterial strains from Chinese patient blood samples, including S. aureus , E. coli , K. pneumoniae , and S. typhi . In addition, Ozbak [ 8 ] showed that the most commonly isolated bacteria in Saudi Arabia were S. aureus and CoNS, among the gram-positive, and E. coli , K. pneumoniae , and P. aeruginosa , among the gram-negative. Moreover, Akova [ 16 ] reported that E. faecium , S. aureus , K. pneumoniae , A. baumannii , P. aeruginosa , E. coli , and Enterobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, every year, three million babies and one million patients suffer from sepsis [ 6 , 7 ]. Between 1981 and 2015, the proportion of BSIs in Saudi Arabia ranged from 1% to 11% in patients with confirmed infections [ 8 ]. In addition, among the Gulf Cooperation Council hospitals, the risk of acquiring central line-associated BSIs was 146% greater than that in the US National Healthcare Safety Network hospitals, but 33% lower than that in the National Health Commission of China hospitals [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation